Correlates of smoking initiation among adolescents 10-17 years old, Brgy 704, San Andres, Manila March, 1999 - Galvez, Eleanor J. (2000)
Adolescence is the time of life when most tobacco users begin and establish smoking behavior. In this cross-sectional study, we examine whether environmental factors are associated with the onset of smoking among adolescents.An interview schedule consisting of 42 questions on socio-demographic, individual characteristics, and environmental factors was administered to 1200 adolescents in Brgy. 704, San Andres, Manila. A participant was considered a smoking initiator if he had puffed one or more cigarettes at the time of interview.Nearly 42of the subjects initiated smoking. The prevalence was highest among the 16-17 years old, males, higher education, lowest socio-economic status, lowest self-esteem and self-efficacy and high intention to smoke. The odds of smoking initiation were higher among adolescents with poor perception about parental skills, whose parents were smoking, those with smoking friends and those with exposure to media influence.Parental, peer and media influence were significant correlates in the smoking initiation process. Certain variables modified the relationship between these environmental factors and smoking initiation.A well-concerted, complementary anti-smoking strategy involving the school and community is essential in preventing an adolescent to begin smoking. The family is a critical component in the maintenance of a non-smoking behavior in this age group.
Thesis (MS Public Health, Epidemiology)--University of the Philippines Manila.
Keywords: Smoking; Teenagers